Sero-diagnosis of Dengue virus in Different Hospitals of Nepal - Shah, Y; Khadka, G; Gupta, GP; Adhikari, N; Poudel, A; Pant, KP; Dahal, B; Pandey, BD (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Dengue fever (DF) is an emerging mosquito borne viral disease and important public health problem in low land Terai region which is also moving towards hilly region Nepal. This study was designed to determine the sero-prevalence of dengue virus infection in patients visiting hospitals of Nepal. MATERIALS AND METHODS: This study was conducted during period (June-November) of 2010 in Nepalese patients with fever visiting hospitals of Birganj, Damouli, Biratanagar, Dhading Besi and Chitwan. The sero-prevalence of dengue virus specific IgM was determined by enzyme linked immunosorbent assay (ELISA). Serum samples were collected from 289 patients visiting hospitals with history of fever and clinically suspected dengue fever. RESULTS: The anti-dengue IgM positivity was found to be 8.99%. The positive dengue cases were higher in male (10.8%) as compared to female (7.1%) though it was not statistically significant (P>0.05). Among different age groups, the highest positive cases (12.3%) were from age group below 15 years followed by above 50 years 8.3%. Out of 5 hospitals, the highest positive cases were in Tanahu hospital, Damouli (23.8%) followed by Bharatpur hospital and Chitwan (22.2%). Age and gender were found to be independent predictors. The highest numbers of dengue positive cases were in occupation group business (13.3%) followed by agriculture (12.7%). CONCLUSIONS: Prevalence of dengue virus infection is increasing and proper control measure should be provided. IgM capture ELISA was used for laboratory analysis and remains as a reliable and inexpensive method for the diagnosis of dengue. Hence, the IgM capture ELISA has become the most accepted technique for the diagnosis of dengue in developing countries like Nepal. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7003 Int J Infect Microbiol 2012;1(1):58-62